2022
DOI: 10.1038/s41598-022-09930-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluating and modeling of SARS-CoV-2 UVC disinfection

Abstract: The ongoing COVID-19 global pandemic has necessitated evaluating various disinfection technologies for reducing viral transmission in public settings. Ultraviolet (UV) radiation can inactivate pathogens and viruses but more insight is needed into the performance of different UV wavelengths and their applications. We observed greater than a 3-log reduction of SARS-CoV-2 infectivity with a dose of 12.5 mJ/cm2 of 254 nm UV light when the viruses were suspended in PBS, while a dose of 25 mJ/cm2 was necessary to ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
9
1
Order By: Relevance
“…The inactivation ability of UV at different wavelengths follows the order of UV 280 > UV 270 > UV 260 > UV 254 > UV 290 > UV 222 . The difference with our conclusion might be related to different absorption and scattering effects of different kinds of protein and suspended materials in the medium for UV irradiation at the same wavelength . For the dried samples, droplets of viral suspension were typically dried at room temperature in the air.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The inactivation ability of UV at different wavelengths follows the order of UV 280 > UV 270 > UV 260 > UV 254 > UV 290 > UV 222 . The difference with our conclusion might be related to different absorption and scattering effects of different kinds of protein and suspended materials in the medium for UV irradiation at the same wavelength . For the dried samples, droplets of viral suspension were typically dried at room temperature in the air.…”
Section: Resultscontrasting
confidence: 64%
“…16 The difference with our conclusion might be related to different absorption and scattering effects of different kinds of protein and suspended materials in the medium for UV irradiation at the same wavelength. 40 For the dried samples, droplets of viral suspension were typically dried at room temperature in the air. Then the dried samples were resuspended to measure virus titers, thus excluding the titer reduction of samples during the drying process.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The higher persistence of viruses in the confined space of the ATMs is likely due to the fact that shielded surfaces are not exposed to direct UV-C light and disinfectants that can, if not destroy, then at least effectively deactivate these viruses. Recent studies devoted to checking the ability of SARS-CoV-2 survival on inanimate surfaces, such as plastic, stainless steel and glass, revealed that UV-C irradiation is highly effective in inactivating SARS-CoV-2 replication, and thus can provide rapid, efficient, and sustainable sanitization of these surfaces [34,35,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that control measures must be taken beyond personal hygiene. UVC radiation is already well known to effectively kill bacteria and viruses [ 11 ] and recent studies have shown that this method is effective in inactivating the SARS-CoV-2 virus [ 12 , 13 , 14 , 15 , 16 ]. UVC light causes the formation of pyrimidine dimers in the genetic material and inhibits transcription and replication [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%